Establishing the research priorities of ADHD professionals: an international Delphi study - Stephens, Kate; Sciberras, Emma; Bisset, Matthew; Summerton, Ainsley; Coghill, David; Middeldorp, Christel M; Payne, Leanne; Bellgrove, Mark A; Faraone, Stephen V.; Banaschewski, Tobias; Newcorn, Jeffery H.; Espinet, Stacey D.; et al. (Journal of attention disorders, 2025)
Objectives: To determine ADHD research priorities from the perspective of ADHD professionals internationally. - Method: A two-stage modified Delphi design was used. In Stage 1 (qualitative), participants listed research questions relating to ADHD that they perceived to be most important (N = 132). In Stage 2 (quantitative), participants were then asked to rate each research question that was deemed appropriate (able to be researched and not already addressed by research) in terms of perceived importance (N = 180). - Results: Stage 1 generated 382 research questions with 10 broad areas identified for example, co-occurring conditions and treatment, etc. The top 20 most important questions related to ADHD in women/girls, long-term medication use, non-pharmacological interventions, ADHD measurement/rating scales, and efficacy of emotional regulation interventions. - Conclusion: These results can inform an ADHD research agenda which represents the views of the individuals from major ADHD professional groups internationally. Parallel work is needed focusing on research priorities from the perspective of ADHD consumers.